2016
DOI: 10.22436/jnsa.009.05.20
|View full text |Cite
|
Sign up to set email alerts
|

Epidemic dynamics on a delayed multi-group heroin epidemic model with nonlinear incidence rate

Abstract: For a multi-group Heroin epidemic model with nonlinear incidence rate and distributed delays, we study some aspects of its global dynamics. By a rigorous analysis of the model, we establish that the model demonstrates a sharp threshold property, completely determined by the values of 0 : if 0 ≤ 1, then the drug-free equilibrium is globally asymptotically stable; if 0 > 1, then there exists a unique endemic equilibrium and it is globally asymptotically stable. A matrix-theoretic method based on the Perron eigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Since r(Ψ [0]) > 1, from the continuity, without loss of generality, we can assume that and λ are sufficiently small and T is sufficiently large such that r(Ψ ,T,λ ) > 1. By (21), as in the proof of Theorem 5.2, we can prove thatĴ 1 [λ] =Ĵ 2 [λ] = 0. This contradicts to the positivity of the solution for u 0 ∈ Ω 0 .…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Since r(Ψ [0]) > 1, from the continuity, without loss of generality, we can assume that and λ are sufficiently small and T is sufficiently large such that r(Ψ ,T,λ ) > 1. By (21), as in the proof of Theorem 5.2, we can prove thatĴ 1 [λ] =Ĵ 2 [λ] = 0. This contradicts to the positivity of the solution for u 0 ∈ Ω 0 .…”
mentioning
confidence: 81%
“…In [19], Liu and Zhang studied the global behavior of a heroin epidemic model with distributed time delay: the drug-free equilibrium is globally asymptotically stable if the basic reproduction number R 0 is less than 1, whereas a disease endemic equilibrium is locally asymptotically stable and the system is uniformly persistent if R 0 > 1. For other studies on the drug epidemic models with time delay, see, e.g., [9,13,20,21].…”
mentioning
confidence: 99%
“…Making the substitution v 1 � ω 2 1 , equation 13can be rewritten as v 4 1 + e 13 v 3 1 + e 12 v 2 1 + e 11 v 1 + e 10 � 0.…”
Section: The Existence Of Hopf Bifurcationmentioning
confidence: 99%
“…Increased use of heroin and other addictive drugs is an issue of concern all over the world. Drug abuse a ects not only life quality of the general public but also the overall situation of social stability and economic development [1][2][3]. e data from the World Drug Report published by the United Nations (U.N.) showed that thirty-ve million people worldwide su er from drug abuse disorders, and only one-seventh has received treatment [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation